Successful treatment of massive hemothorax with class IV shock using aortography with transcatheter embolization of actively bleeding posterior left intercostal arteries after penetrating left chest trauma: A case for the hybrid OR. (2018) - Moore, Carolyn; Kwayisi, Golda; Esiobu, Prince; Bashan-Gilzenrat, Keren A.; Matthews, Leslie R.; Nguyen, Jonathan; Moriarty, Nathaniel; Liggon, Michael; Udobi, Kahdi; Taha, Assad; Childs, Ed; Danner, Omar
Highlights: We present a case of a 19 year old male with massive hemothorax and refractory, class IV hemorrhagic shock due to proximal left posterior intercostal artery injury with uncontrollable bleeding secondary to a left chest gunshot wound in the 4th intercostal space (ICS). The patient was emergently taken to the operating room for thoracotomy and left chest exploration and found to have massive ongoing massive from his left posterior chest with severe hemodynamic instability and profound levels of hemorrhagic shock. Despite multiple attempts to surgically stop the bleeding intraoperatively as well as using various hemostatic measures, we were unable to control the excessive bleeding. The patient developed refractory class IV hemorrhagic shock with sinus tachycardia to the 170′s and persistent hypotension with systolic blood pressures in the 70′s, which was not amenable to surgical control. Consequently, the patient was taken to the angiography suite in radiology where thoracic aortography was performed and revealed active bleeding from the left 7th posterior intercostal artery < 3 cm from the aorta. The patient underwent thoracic angiography with percutaneous catheter-based embolization of the bleeding intercostal artery. The bleeding arterial segment was controlled with coils and gelfoam along with the vessels immediately above and below the area of extravasation. The patient's hemodynamics significantly stabilized. He was transferred to the surgical ICU for ongoing resuscitation. The patient survived and was ultimately discharged to home in satisfactory condition. This is the first report in the literature of using thoracic angiography with selective catheter based embolization to arrest bleeding of an injured posterior intercostal artery due to penetrating injury or gunshot wound of the chest. Abstract: Hemothorax is a common occurrence after blunt or penetrating injury to the chest. Posterior intercostal vessel hemorrhage as a cause of major intrathoracic bleeding is an infrequent source of massive bleeding. Selective angiography with trans-catheter embolization may provide a minimally invasive and efficient method of controlling bleeding refractory to surgical treatment. Presentation of case: A 19 year-old male sustained a gunshot wound to his left chest with massive hemothorax and refractory hemorrhage. He was emergently taken to the operating room for thoracotomy and was found to have uncontrollable bleeding from the chest due to left posterior intercostal artery transection. The bleeding persisted despite multiple attempts with sutures, clips and various hemostatic agents. Thoracic aortography was undertaken and revealed active bleeding from the left 7th posterior intercostal artery, which was coil-embolized. The patient's hemodynamic status significantly improved and he was transferred to the intensive care unit. Discussion: Posterior intercostal bleeding is a rare cause of massive hemothorax. Bleeding from these arteries may be difficult to control due to limited exposure in that area. Transcatheter-based arterial embolization is a reliable and feasible option for arresting hemorrhage following failed attempts at hemorrhage control from thoracotomy. Conclusion: Massive hemothorax from intercostal arterial bleeding is a rare complication after penetrating chest injury (Aoki et al., 2003). Selective, catheter-based embolization is a useful therapeutic option for hemorrhage control and can be expeditiously employed if a hybrid operating room is available.